Neurons and Astrocytes Elicit Brain Region Specific Transcriptional Responses to Prion Disease in the Murine CA1 and Thalamus - Slota, Jessy A.; Medina, Sarah J.; Frost, Kathy L.; Booth, Stephanie A. (Frontiers in Neuroscience, 2022)
Progressive dysfunction and loss of neurons ultimately culminates in the symptoms and eventual fatality of prion disease, yet the pathways and mechanisms that lead to neuronal degeneration remain elusive. Here, we used RNAseq to profile transcriptional changes in microdissected CA1 and thalamus brain tissues from prion infected mice. Numerous transcripts were altered during clinical disease, whereas very few transcripts were reliably altered at pre-clinical time points. Prion altered transcripts were assigned to broadly defined brain cell types and we noted a strong transcriptional signature that was affiliated with reactive microglia and astrocytes. While very few neuronal transcripts were common between the CA1 and thalamus, we described transcriptional changes in both regions that were related to synaptic dysfunction. Using transcriptional profiling to compare how different neuronal populations respond during prion disease may help decipher mechanisms that lead to neuronal demise and should be investigated with greater detail.